2019
DOI: 10.1002/ccd.28306
|View full text |Cite
|
Sign up to set email alerts
|

PK Papyrus covered stent: Device description and early experience for the treatment of coronary artery perforations

Abstract: Background Coronary artery perforation during percutaneous revascularization is associated with considerable morbidity and mortality. The PK Papyrus covered stent provides a physical barrier to seal perforated arteries and prevent associated complications including death. Methods In a survey of patients treated for coronary artery perforation with the PK Papyrus stent in 16 countries, procedural and in‐hospital outcomes were ascertained. Procedural variables included device delivery, sealing of the perforation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Amorphous SiC has recently been tested in various neural prosthetic applications not only as a conformal encapsulation material [36,58,63] but also as adhesion-promoting layer of a polymer coating [63,64] and as both substrate and an insulating material of neural interfaces, enabling all-SiC devices [65,66]. Additionally, a-SiC has been used in a recently regulatory approved cardiac stent [67].…”
Section: Inorganic Materialsmentioning
confidence: 99%
“…Amorphous SiC has recently been tested in various neural prosthetic applications not only as a conformal encapsulation material [36,58,63] but also as adhesion-promoting layer of a polymer coating [63,64] and as both substrate and an insulating material of neural interfaces, enabling all-SiC devices [65,66]. Additionally, a-SiC has been used in a recently regulatory approved cardiac stent [67].…”
Section: Inorganic Materialsmentioning
confidence: 99%
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the performance in the long term was poor due to the high incidence of ISR (25%) and ST (from 3% to 16%) [ 16 18 ]. The PK Papyrus CS (Biotronik, USA) was a cobalt-chrome stent platform covered with a single-layer of PU material [ 19 ]. Hernandez-Enriquez et al came to an encouraging conclusion that delivery time of PK Papyrus stent was shorter and brought about reduced frequency of pericardial effusion and cardiac arrest in comparison with the Graftmaster [ 20 ].…”
Section: Discussionmentioning
confidence: 99%